The previous question was:

Find the fourier coefficients of $f(x)=x^2+1$

To which I found $a_0=\frac{\pi^2}{3}+1$ and $a_n=\frac{2}{n^2}(-1)^n$ (I am unsure on $b_n$ I get $b_n=(\frac{-2}{n\pi}-\frac{2\pi}{n}+\frac{4}{n^3\pi})(-1)^n$ but this is more method than correcting that)

I want to complete the next part:

By considering the derivative of $f$, write down the fourier series of $g(x)=x $ without explicitly calculating the coefficients

So as $\frac{1}{2}f'(x)=g(x)$ I get (again ignoring $b_n$ for now):

\begin{align} g(x) & =\frac{1}{2}\int_{-\pi}^\pi \left(\frac{\pi^2}{3} + 1 + \sum_{n=1}^\infty \frac{2}{n^2} (-1)^n\cos(nx)\,dx\right) \\[10pt] & =\frac{1}{2} \left[\frac{\pi^2x}{3} + x + \sum_{n=1}^\infty \frac{2}{n^3}(-1)^n\cos(nx)\right]_{-\pi}^\pi =\frac{2\pi^3}{6} + \frac{\pi}{2} + \sum_{n=1}^\infty \frac{1}{n^3} \end{align}

Is this correct?

  • $\begingroup$ You have $g(x) = \text{an expression with no }x\text{ in it.}$ That can't be right. $\qquad$ $\endgroup$ – Michael Hardy Aug 16 '16 at 11:51

Firstly: $f(x)$ is an even function, so you expect all $b_n = 0$.

Now for $g(x)$. You are right to note that $g(x) = \frac{1}{2} f'(x)$, but why are you integrating? Futhermore: the last equation: LHS is a function of $x$ and RHS is just a constant.

To solve the problem write $f(x)$ as a sum of cosines (so in in it's Fourier form), take the derivative and then divide by $2$ to get $g(x)$. From there you can get the coefficients without much hustle.

  • $\begingroup$ Oh yeah obviously I should have differentiated not integrated! So $$g(x)=\frac{1}{2} \frac{dn}{dx} \frac{\pi^2}{3} + 1 + \sum_{n=1}^\infty \frac{2}{n^2} (-1)^n\cos(nx)= \sum_{n=1}^{\infty} -n\frac{2}{n^2} (-1)^n\sin(nx)$$ $\endgroup$ – Lauren Aug 16 '16 at 12:03
  • $\begingroup$ Note how your expression now has $\frac{1}{n}$ in it. This corresponds to power of x in your function. $x^2$ will give you $\frac{1}{n^2}$ etc etc. Next thing: when asking for Fourier series you should always state the interval. Right now you are working on $[-\pi, \pi]$. $\endgroup$ – Piotr Benedysiuk Aug 16 '16 at 12:36
  • $\begingroup$ From $\sum_{n=1}^{\infty}\frac{-2}{n}(-1)^n \sin (nx)$ how do I then put this into the standard $g(x)=a_0+\sum_{n=1}^{\infty}a_n \cos (nx) + b_n \sin (nx)$ form? $\endgroup$ – Lauren Aug 16 '16 at 13:25
  • $\begingroup$ Realize that $g(x) = \sum\limits_{n =1}^{\infty} \frac{-2}{n} (-1)^n \sin(nx)$ is already in standard form. What then must $a_0$, $a_n$ and $b_n$ be? $\endgroup$ – Piotr Benedysiuk Aug 16 '16 at 16:39

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.